If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(t + -3) + 7t = 4t + -2 Reorder the terms: -5(-3 + t) + 7t = 4t + -2 (-3 * -5 + t * -5) + 7t = 4t + -2 (15 + -5t) + 7t = 4t + -2 Combine like terms: -5t + 7t = 2t 15 + 2t = 4t + -2 Reorder the terms: 15 + 2t = -2 + 4t Solving 15 + 2t = -2 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 15 + 2t + -4t = -2 + 4t + -4t Combine like terms: 2t + -4t = -2t 15 + -2t = -2 + 4t + -4t Combine like terms: 4t + -4t = 0 15 + -2t = -2 + 0 15 + -2t = -2 Add '-15' to each side of the equation. 15 + -15 + -2t = -2 + -15 Combine like terms: 15 + -15 = 0 0 + -2t = -2 + -15 -2t = -2 + -15 Combine like terms: -2 + -15 = -17 -2t = -17 Divide each side by '-2'. t = 8.5 Simplifying t = 8.5
| 10p+9+11=-2(2p+4)-3(2p-2) | | (x+3)2-4=0 | | 6n+12=78 | | -7=-7.5z-(-7z+3) | | log[4](2x-9)-log[4](x-8)=3 | | 3(x+9)=6x | | 2=x-4(2x+3) | | 8(r+2)=54 | | 7x=12x-45 | | (+15)+(-7)+(+1)= | | y=57-2 | | 2x+4x=3x+3 | | 3(x-9)=6x | | 1/5y=9-2/5y | | 4c-6=-2 | | 2n+5+4=-1 | | 4C-6=two | | xb=ya | | 2x=11+x | | 6x+1=6(x+1) | | Y=0.15x+0.55 | | 5(15+x)=-70 | | 2*5+8/2=18 | | 2.49+x= | | 9x+1/3x=0 | | 0.20(y-4)+0.16y=0.02y-0.07(60) | | 9x+3x=0 | | (4b+3b^4)-(2b-8b^4)+(5b+9b^2+6b^4)= | | 0.2m=0.3m+2.4 | | 16x^2+32x-65=0 | | m+33=112 | | -12+12=y |